Research on Data Visualization Design Based on Big Data - Scott, Samuel; Adams, Lily; Baker, Jackson (Journal of Computer Science and Software Applications, 2023)
This study addresses the technical domain of big data applications, focusing on data visualization design research based on big data. The methodology includes collecting or inputting raw data, preprocessing and storing the data to obtain precise initial data, visually matching the preprocessed data, completing data modeling, creating and designing visual charts, and presenting the data visually. The aim of this research is to enhance data visualization design by optimizing data processing methods and utilizing the automatic analysis and production capabilities of computers. This approach enables a more intuitive and efficient understanding of the information, knowledge, and insights derived from big data.